Efeitos do treinamento isocinético e isométrico sobre a taxa de desenvolvimento de força máxima - Oliveira, Felipe Bruno Dias de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The objective of the present study was to compare the effects of a high speed isokinetic training (180°.s-1) and an isometric training (75°) on the maximum rate of force development (RFDmax) measured in the isokinetic and isometric modes. Twenty seven male non active subjects participated of this study (Mean + SD = body mass 78.6 + 14.1 kg; stature 175.1 + 8.9 cm; age 22.6 + 3.8 years). They were randomly divided into three groups: Control (GC); Isokinetic training (GISOC) and; Isometric training (GISOM). The subjects were submitted in different days to the following pre training protocols: 1) Familiarization to the isokinetic dynamometer tests; 2) Five maximum concentric isokinetic contractions of the knee extensors (180°.s-1) to access the maximum concentric torque (TMC) and the concentric RFDmax; 3) Two maximum isometric contractions of the knee extensors (75°) to access the maximum isometric torque (TMI) and the isometric RFDmax. The same tests were repeated after the training period, but without the familiarization session. Eighteen training sessions were performed (3 times per week). The GISOC performed the entire training whit concentric isokinetic contractions whit the speed of 180°.s-1. The GISOM performed the entire training whit isometric contractions whit the angle between the thigh end the leg being 75° (0° = full knee extension). TMI, TMC, concentric RFDmax, isometric RFDmax values of the GC was not different between pre and post training. GISOM increased only the TMI and the GSIOC increased the TMC, concentric RFDmax and isometric RFDmax. Furthermore, the GISOC had a higher percentage increase of the isometric RFDmax than the isokinetic RFDmax. Based on these results, it is possible to conclude that the increase in maximum strength corresponded to the training specificity theory, unlike to the RFDmax. Thus the use of isometric contraction ...(Complete abstract click electronic access below)

O objetivo do presente estudo foi comparar os efeitos do treinamento isocinético de alta velocidade (180º.s-1) e isométrico (75°) sobre a taxa de desenvolvimento de força máxima (TDFmax) medida de modo isocinético e isométrico em indivíduos sedentários. Participaram deste estudo 27 voluntários do sexo masculino (Média + DP = massa corporal 78,6 + 14,1 kg; altura 175,1 + 8,9 cm; idade 22,6 + 3,8 anos) que foram divididos em três grupos de forma randômica: Controle (GC); Treinamento isocinético (GISOC) e; Treinamento isométrico (GISOM). Os indivíduos foram submetidos, em dias diferentes aos seguintes protocolos de testes pré-treinamento: 1) Familiarização aos testes no dinamômetro isocinético; 2) Cinco contrações isocinéticas concêntricas máximas para os extensores do joelho (180.s-1) para determinar o torque máximo concêntrico (TMC) e a TDFmax concêntrica; 3) Duas contrações isométricas máximas para os extensores do joelho (75°) para determinar o torque máximo isométrico (TMI) e a TDFmax isométrica. Os mesmos testes foram repetidos após o termino do treinamento, mas sem o período de familiarização. Foram realizadas 18 sessões de treinamento (3 vezes por semana). O GISOC realizou todo o treino com contrações isocinéticas concêntricas com velocidade 180°.s-1. O GISOM realizou todo o treino com contrações isométricas com o ângulo entre a coxa e a perna sendo 75° (0° = extensão total do joelho). Os valores de TMI, TMC, TDFmax concêntrica, TDFmax isométrica do GC não foi diferente estatisticamente entre o período pré e póstreinamento. O GISOM melhorou apenas o TMI e o GISOC melhorou o TMC, TDFmax concêntrica e TDFmax isométrica. Além disso, o GISOC melhorou percentualmente mais a TDFmax concêntrica do que a TDFmax isométrica. Com base nestes resultados pode-se concluir que...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Esportes - Treinamento técnico; Especificidade; Specificity